In vitro anti-inflammatory and wound healing properties of defatted Selenicereus monacanthus (Lem.) D.R.Hunt seed extract - Zulkifli, Siti Atikah; Abd Gani, Siti Salwa; Zaidan, Uswatun Hasanah; Misran, Azizah; Hassan, Masriana (Taylor and Francis Ltd., 2024)
Extracts from Selenicereus monacanthus (synonym: Hylocereus polyrhizus) have received attention due to their potent anti-inflammatory, antioxidant, anticancer, and antidiabetic properties. The current study aims to determine the anti-inflammatory and wound-healing potential of defatted S. monacanthus seed extract (DSMSE). Anti-inflammatory properties of DSMSE on LPS-induced inflammation on THP-1 were determined by measuring the levels of interleukins IL-6, IL-8, and IL-10. Wound healing scratch assay was performed using the human fibroblast (Hs27) cell that assesses the cell migration over 24 h exposure to DSMSE. Administration of DSMSE significantly reduced the LPS-stimulated release levels of IL-6 and IL-8 and significantly increased the levels of IL-10. Treatment with DSMSE showed a significant increase in wound closure with 70% of fibroblast migration. Therefore, the current study showed the anti-inflammatory and wound healing properties of DSMSE reducing inflammatory cytokines (IL-6 and IL-8), increasing IL-10 cytokine, and increasing wound closure at 24 h.